PERANAN K3 PADA PEKERJAAN PEMELIHARAAN MESIN DIESEL RIG CARRIER C15 DENGAN MENGGUNAKAN METODE HIRARC: SEBUAH STUDI KASUS - Nazar, Iqbal; Ashari , Faisal (J-ENSITEC (Journal of Engineering and Sustainable Technology), 2025)
Occupational Health and Safety (OHS) is a crucial aspect of every work activity, especially in the maintenance of heavy machinery such as the Diesel Rig Carrier CAT-15. This study aims to identify potential hazards, assess risk levels, and determine appropriate control measures using the HIRARC (Hazard Identification, Risk Assessment, and Risk Control) method in the maintenance activities of the Diesel Rig CAT-15 at PT. Tiga Musim Mas Jaya.The research method involved direct observation and analysis of nine main maintenance activities, namely checking the radiator, engine oil, transmission oil, hydraulic tank, spark arrestor, battery voltage, V-belt, Eagle box, and flywheel. The hazard identification results found a total of 29 potential hazards with varying risk levels: 37.93% categorized as low risk, 44.83% as medium risk, and 17.24% as high risk. Following the implementation of risk controls based on the hierarchy of controls (elimination, substitution, engineering design, administrative measures, and the use of Personal Protective Equipment/PPE), all potential risks were successfully reduced to a low level.The conclusion of this study indicates that the systematic application of the HIRARC method can enhance the effectiveness of risk control and contribute to creating a safe and healthy work environment for employees. This approach is expected to be continuously implemented as part of the company’s OHS management system.